Maternal and fetal outcome in pregnancy with advanced maternal age- a prospective study - Thayyil, Neha A.; Radha, Sreekumari; Kartha, Niveditha; Serbin, Shalima; John, Bimal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Advanced maternal age defined as the age of mother ≥35 years at the time of delivery has become common in last two to three decades. It is considered to have more adverse obstetric and perinatal outcomes as compared to those in younger women. Therefore, it requires a proper understanding of the effect of age during her antepartum, intrapartum, and postpartum period that prevent a healthy outcome. Methods: The primary objective was to study the maternal and foetal outcome of pregnancy in women aged ≥ 35 years. This was a prospective observational study conducted in 122 pregnant women over a duration of 18 months in the multispecialty hospital in an urban setting. Results: In this study, pregnant women aged ≥35 years had a higher incidence of obesity (88.9%). Among antenatal complications, mothers aged ≥35 years had higher incidence of anaemia (21.3%), gestational diabetes mellitus (GDM) (37.7%), gestational hypertension (32.8%), fetal growth restriction (13.1%). There was no significant difference in the incidence of miscarriage, multiple pregnancy, malpresentation, preterm premature rupture of membranes (PPROM), intrauterine fetal demise between the two age groups. The incidence of preterm delivery (41%) and caesarean section (72.4%) were higher in advanced age group. Perinatal complications like low birth weight (29.3%), neonatal intensive care unit (NICU) admissions (32.8%) were higher in neonates of women aged ≥35 years. Conclusions: Advanced maternal age was significantly associated with adverse obstetrical and fetal complications. Therefore, proper preconceptional counselling and intensive antenatal care assessment can individualize and potentially reduce the risks for women with advanced maternal age.